2012
DOI: 10.1002/jssc.201100726
|View full text |Cite
|
Sign up to set email alerts
|

Application of solid‐phase microextraction and gas chromatography‐mass spectrometry for the determination of chlorophenols in leather

Abstract: This paper proposes a new analytical procedure based on the headspace solid-phase microextraction (HS-SPME) technique and gas chromatography-selected ion monitoring-mass spectrometry (GC-SIM-MS) for the determination of 16 phenols extracted from leather samples. The optimized conditions for the HS-SPME were obtained through two experimental designs - a two-level fractional factorial design followed by a central composite design - using the commercial SPME fiber polyacrylate 85 μm (PA). The best extraction cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…The results of this study, shown in Figure 2, indicate a reduction in the extraction efficiency of the OCPs when the ionic strength was increased. This finding is in agreement with that reported by Dong [7] , Prates [8] and Pawliszyn [9,10,11] who studied the salting out effect on the extraction of OCPs. Therefore, no salt was added to the vials for the next steps of this study.…”
Section: Optimization Of Extraction Conditionssupporting
confidence: 93%
“…The results of this study, shown in Figure 2, indicate a reduction in the extraction efficiency of the OCPs when the ionic strength was increased. This finding is in agreement with that reported by Dong [7] , Prates [8] and Pawliszyn [9,10,11] who studied the salting out effect on the extraction of OCPs. Therefore, no salt was added to the vials for the next steps of this study.…”
Section: Optimization Of Extraction Conditionssupporting
confidence: 93%
“…It has been demonstrated that LiChrolut-EN has a much stronger retention of volatiles than other commonly used sorbents, such as bond Elut ENV (styrene- divinylbenzene), Amberlite, and Tenax TA [ 20 , 21 ]. Another commonly used technique is solid phase microextraction (SPME), which can extract volatile and semi-volatile organic compounds from environmental, biological, and food samples [ 22 , 23 , 24 ]. There are also a lot of commercially available stationary phases, although the divinylbenenze/carboxen/polydimethylsiloxane (DVB/CAR/PDMS) is the most frequently used on an expanded range of analytes.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, application of one‐variable‐at‐a‐time optimization method has some disadvantages, including tediousness and inability to predict interaction among factors. Experimental design (full or fractional factorial design) have been used for optimization of microextraction methods and prediction of the main and interaction effects . Based on the preliminary studies, six variables including amount of adsorbent, eluent volume, ultrasound time, ionic strength, desorption time and aqueous sample volume were considered.…”
Section: Resultsmentioning
confidence: 99%